Diagnostic potential of hepcidin testing in pediatrics. (26th February 2013) - Cangemi, Giuliana; Pistorio, Angela; Miano, Maurizio; Gattorno, Marco; Acquila, Maura; Bicocchi, Maria Patrizia; Gastaldi, Roberto; Riccardi, Francesca; Gatti, Cinzia; Fioredda, Francesca; Calvillo, Michaela; Melioli, Giovanni; et al.
Abstract Objectives Hepcidin, a peptide hormone released by hepatocytes into circulation is the main regulator of dietary iron absorption and cellular iron release. Although commercial tests are available, assay harmonization for hepcidin has not been yet reached, making reference intervals and consequent clinical decisions still elusive for each assay and specific population. The aim of this study is to set up hepcidin measurement in pediatric age and to investigate its potential usefulness in the diagnosis and management of iron disorders in children. Methods Serum hepcidin was measured by using an automated commercial immunoassay. Reference values were obtained from 86 healthy children. Hepcidin was then evaluated in 52 children with diseases where this hormone was expected to be differently regulated. Results Hepcidin values were 43.6 ng/mL median; 32–52.7 1–3 q: in males and 36.4 ng/mL median; 28.5–45.7 1–3 q: in females (P = 0.039). Hepcidin was significantly higher in postpubertal normal females than in normal males. Hepcidin resulted up‐regulated in anemia of chronic disease of children affected by systemic Juvenile Idiopathic Arthritis and decreased after treatment with anakinra, an anti‐interleukin‐1 receptor antagonist. In iron deficiency anemia patients on oral iron supplementation and in β‐thalassemia subjects, hepcidin levels were similar to those found in healthy subjects. Conclusions This study sets up reference values for pediatric population and shows that in normal controls serum hepcidin react differently to puberty in females vs. males. In addition, it suggests that serum hepcidin may discriminate microcytic inflammatory anemia of Juvenile Idiopathic Arthritis from iron deficiency anemia. Overall these findings may represent a helpful tool for future studies tailored to understand the role of hepcidin in management of iron disorders in children.